2010
DOI: 10.1051/0004-6361/200912731
|View full text |Cite
|
Sign up to set email alerts
|

$\ion{H}{i}$ and CO in the circumstellar environment of the S-type star RS Cancri

Abstract: Context. The history of mass loss during the AGB phase is key to understanding the stellar evolution and the gas and dust replenishment of the interstellar medium. The mass-loss phenomenon presents fluctuations with a wide variety of timescales and spatial scales and requires combining data from multiple tracers. Aims. We study the respective contributions of the central source and of the external medium to the complex geometry of circumstellar ejecta. Methods. This paper presents Plateau de Bure Interferomete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 43 publications
(72 reference statements)
10
50
1
Order By: Relevance
“…The H i line at 21 cm has proved to be an excellent spatio-kinematic tracer of the external regions of circumstellar shells (e.g., Matthews & Reid 2007). In particular, the H i map of RS Cnc presented by Matthews & Reid shows a 6 -long tail, in a direction opposite to the space motion of the central star, and clearly different from that of the bipolar flow observed in CO at shorter distances (2-10 ) by Libert et al (2010). In such a case the shaping mechanism is thought to be due to the motion of the star relative to the local interstellar medium Matthews et al 2013).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…The H i line at 21 cm has proved to be an excellent spatio-kinematic tracer of the external regions of circumstellar shells (e.g., Matthews & Reid 2007). In particular, the H i map of RS Cnc presented by Matthews & Reid shows a 6 -long tail, in a direction opposite to the space motion of the central star, and clearly different from that of the bipolar flow observed in CO at shorter distances (2-10 ) by Libert et al (2010). In such a case the shaping mechanism is thought to be due to the motion of the star relative to the local interstellar medium Matthews et al 2013).…”
Section: Introductionmentioning
confidence: 86%
“…Summary of previous data RS Cnc was imaged in the CO1−0 and 2−1 lines by Libert et al (2010). An on-the-fly (OTF) map covering a region of 100 × 100 with steps of 4 in RA and 5 in Dec was obtained at the IRAM 30 m telescope.…”
Section: Co Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of them show oblate, even very flat structures, but without any sign of rotation in the observations. This is the case of axisymmetric shells around semiregular variables (e.g., Libert et al 2010;Castro-Carrizo et al 2010) and of flat equatorial structures that are often found in bipolar PPNe (e.g. Alcolea et al 2007;Castro-Carrizo et al 2002, 2012.…”
Section: Introductionmentioning
confidence: 99%